The Effect of Working Capital Management with Net Operating Profit of Manufacturing Companies - Hassan Nikseresht; Mohammad Taghipour (International Journal of Trends in Humanities, 2024)
This study attempts to show the impact of working capital management on operating profit for manufacturing organizations in order to reach profit targets and increase sales. Additionally, it seeks to determine whether working capital management significantly affects a company's operating net profit. Working capital management factors such as average collection period, daily balance turnover, average payment period, cash conversion cycle, and net exchange turnover of the business are considered in this study. In this research, the main independent variable "working capital management" and the dependent variable "operational net profit"; And the location of this research was the companies accepted in the Tehran Stock Exchange in the Islamic Republic of Iran in the period of the year (2010-1382). Then, by estimating the working capital management items, its effect on profitability is adapted to the relevant industry, and at the end, the relationships between the research variables are analyzed by running a regression model. The findings of the research show that working capital management has a relationship with net operating profit and also the company's working capital management has a significant relationship with the operating net profit of manufacturing companies. The results show a strong positive correlation between net operating profit and efficient working capital management, underscoring the critical role that working capital management plays in improving the financial performance of manufacturing firms.
Keywords: Average Collection Period; Inventory turnover per day; Net Exchange Turnover; Net Operating Profit; Working Capital Management